Effects of household washing on bacterial load and removal of Escherichia coli from lettuce and "ready‐to‐eat" salads. Issue 6 (20th September 2017) - Uhlig, Elisabeth; Olsson, Crister; He, Jiayi; Stark, Therese; Sadowska, Zuzanna; Molin, Göran; Ahrné, Siv; Alsanius, Beatrix; Håkansson, Åsa
Abstract: Customer demands for fresh salads are increasing, but leafy green vegetables have also been linked to food‐borne illness due to pathogens such as Escherichia coli O157:H7. As a safety measure, consumers often wash leafy vegetables in water before consumption. In this study, we analyzed the efficiency of household washing to reduce the bacterial content. Romaine lettuce and ready‐to‐eat mixed salad were washed several times in flowing water at different rates and by immersing the leaves in water. Lettuce was also inoculated with E. coli before washing. Only washing in a high flow rate (8 L/min) resulted in statistically significant reductions ( p  < .05), "Total aerobic count" was reduced by 80%, and Enterobacteriaceae count was reduced by 68% after the first rinse. The number of contaminating E. coli was not significantly reduced. The dominating part of the culturable microbiota of the washed lettuce was identified by rRNA 16S sequencing of randomly picked colonies. The majority belonged to Pseudomonadaceae, but isolates from Enterobacteriaceae and Staphylococcaceaceae were also frequently found. This study shows the inefficiency of tap water washing methods available for the consumer when it comes to removal of bacteria from lettuce. Even after washing, the lettuce contained high levels of bacteria that in a high dose and under certain circumstances may constitute a health risk. Abstract : Leafy green vegetables are often linked to food‐borne illness, and consumers often wash these products at home as a safety measure. The efficiency of household washing to reduce the bacterial content was analyzed with and without E. coli inoculation, and only washing in a high flow rate (8 L/min) without E. coli resulted in statistically significant reductions. This study shows the inefficiency of tap water washing methods available for the consumer, and even after washing, the products contained high levels of bacteria that in a high dose and under certain circumstances may cause illness.